2020
DOI: 10.1186/s12909-020-1958-3
|View full text |Cite
|
Sign up to set email alerts
|

Raising awareness about microbial antibiotic resistance in undergraduate dental students: a research-based strategy for teaching non-laboratory elements of a microbiology curriculum

Abstract: Background: Resistance to antimicrobial agents has become a problem in modern society. Antibiotic resistant bacteria undermine the prevention and treatment of infections. Undergraduate dental students in Europe are required to receive information in aspects of microbiology relevant for dental practice, including oral microbial pathogens and resistance mechanisms against antimicrobial compounds. The objective of this study was to implement a research-based strategy to aid the understanding of the increase in an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Higuita-Gutiérrez and colleagues, reported in 2020 that medical students from three medical schools in Medellin, Colombia exhibit poor knowledge regarding antibiotic use due to insufficient training with regard to antibiotic use and bacterial resistance [34]. Whereas, Veses and colleagues in the same year, after surveying undergraduate dental students at Universidad Cardenal Herrera, concluded that awareness campaigns are needed to promote student's use of antibiotics in young generations particularly among the pre-professional health sciences students [35]. Interestingly, as a result of the lack of training they discovered, Tsopra et al 2020 used a game called 'AntibioGame' through which students play the role of a doctor meeting patients in consultation as a promising tool for improving knowledge in antibiotic prescription [36].…”
Section: Discussionmentioning
confidence: 99%
“…Higuita-Gutiérrez and colleagues, reported in 2020 that medical students from three medical schools in Medellin, Colombia exhibit poor knowledge regarding antibiotic use due to insufficient training with regard to antibiotic use and bacterial resistance [34]. Whereas, Veses and colleagues in the same year, after surveying undergraduate dental students at Universidad Cardenal Herrera, concluded that awareness campaigns are needed to promote student's use of antibiotics in young generations particularly among the pre-professional health sciences students [35]. Interestingly, as a result of the lack of training they discovered, Tsopra et al 2020 used a game called 'AntibioGame' through which students play the role of a doctor meeting patients in consultation as a promising tool for improving knowledge in antibiotic prescription [36].…”
Section: Discussionmentioning
confidence: 99%
“…Project-based strategies for teaching science subjects have also demonstrated positive effects on knowledge acquisition and critical thinking for microbiological analysis methods among undergraduate dental students [43]. In that study, there was no analysis of the scores obtained by the students in their exams, but two questionnaires for evaluating the student learning objectives were used to measure the effect of the strategy.…”
Section: Discussionmentioning
confidence: 99%
“…A survey conducted at CEU Cardenal Herrera University revealed that the inclusion of authentic research experiences in microbiology courses had a positive impact on students. The results indicated improvements in critical thinking skills, knowledge of research design, and a deeper understanding of microbial analysis methods [ 25 ]. Our educational philosophy aligns with this approach, we strongly encourage students with a keen interest in research to approach their tutors and seek opportunities to participate in laboratory work.…”
Section: Discussionmentioning
confidence: 99%